The Influence of School-Based Management and Transforma-tional Leadership on School Quality Mediated by Teacher Professionalism - Agus Prianto; Taufiq Rachman; Anna Wulandari (Yayasan Riset dan Pengembangan Intelektual, 2024)
In the pursuit of understanding effective educational management and leadership, this quantitative study utilizes SmartPLS 3.0 to examine the impact of School-Based Management (SBM) and Transformational Leadership (TL) of school principals on school quality at SMP Presiden Cikarang. Seven hypotheses were tested to elucidate these relationships, focusing on the mediating role of teacher professionalism. The findings highlight significant influences: SBM positively affects school quality, and TL similarly demonstrates a significant positive impact. Furthermore, SBM significantly enhances teacher professionalism, contrasting with TL, which shows no significant impact on teacher professionalism. Additionally, teacher professionalism emerges as a significant contributor to school quality. Notably, SBM, through its enhancement of teacher professionalism, significantly improves school quality. However, TL, when mediated through teacher professionalism, does not exert a significant influence on school quality. These results underscore the critical role of SBM and the nuanced impact of TL in fostering school quality through enhanced teacher professionalism.